Potensi Air Liur Nyamuk sebagai Biomarker Diagnosis Infeksi Dengue - Suharno Zen; Nadya Syarifatul Fajriyah; Ilham Fathurrahman; Miftahuz Zakiyah (Prodi Sains Biomedis Fakultas Ilmu Kesehatan Universitas Muhammadiyah Metro, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. Early diagnosis is essential to reduce the severity and mortality rate of this infection. Recent studies have shown that mosquito saliva contains specific biomarkers that can be used to detect dengue infection non-invasively. This study uses a systematic literature review method, namely tracing and analyzing various scientific publications relevant to the topic of non-invasive diagnostics for dengue. The results of the study can be concluded that: that mosquito saliva has great potential as a source of biomarkers for non-invasive dengue diagnosis. This method can be a more effective and easily accessible solution, especially in dengue endemic areas. However, to increase its effectiveness, further research is needed in the aspects of developing biomarker-based diagnostic kits, validation in various epidemiological environments, integration of this method in the global health system and regulation of policy makers